PENGARUH ARAHAN SHALAT DHUHA TERHADAP KECEMASAN SOSIAL/FOBIA SOSIAL SISWA DI SMP NEGERI 3 PEKANBARU - Beby Andina Syafindri; Syahrilfuddin Syahrilfuddin; Zulfan Saam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of this research is to know the effect of the direction of Dhuha prayer on social anxiety / social phobia of students in SMP Negeri 3 Pekanbaru and to determine the differences in social anxiety / social phobia of students in school before and after the direction of Dhuha prayer. This type of research is a quantitative study with an experimental method using the research design One-Group Pretest-Posttest Design. So that from these differences, can know the influence of the Dhuha prayer direction on social anxiety / student social phobia. The measuring instrument used in this study is the measurement scale of social anxiety / student social phobia which consists of 53 items before the validity, and after divalidity there are 24 valid items obtained with validity of 0.3882 and reliability of 0.887. The subjects of this study amounted to 7 people selected through the results of the non probability sampling in SMP Negeri 3 Pekanbaru which was identified as having social anxiety / social phobia in the very high and high categories. The data processing that has been done can be concluded as follows: social anxiety / social phobia of students before the Dhuha prayer directives, there are five people classified as very high category and two people classified as high category. After being given the Dhuha prayer direction there were changes in social anxiety / social phobia of students in seven people classified as medium category. The directives for performing the Dhuha prayer provide a significant positive effect on social anxiety / student social phobia.Key Words: Direction of Dhuha Prayer, Social Anxiety / Social Phobia